Common Mistakes in Diagnosis of Subchondral Bone Lesions - Gorbachova, Tetyana; Melenevsky, Yulia (Seminars in Musculoskeletal Radiology, 2025)
Non-neoplastic and noninfectious subchondral bone lesions incorporate several entities: acute traumatic injuries, insufficiency and fatigue fractures, primary or secondary osteonecrosis, osteochondritis dissecans, subchondral abnormalities related to cartilage loss, and marrow changes accompanying disuse or other causes of accelerated bone remodeling. Differentiating these conditions on imaging can be challenging due to overlapping imaging features, technical aspects, and insufficient clinical history. This review discusses how to avoid common mistakes in the imaging diagnosis of subchondral lesions, focusing on descriptive terminology, imaging scenarios, and reporting key imaging features that affect prognosis in these lesions.
Keywords: subchondral insufficiency fracture; osteonecrosis; osteochondritis dissecans